(untitled) (Qualitative Research Journal for Social Studies, 2026)
This study explores the relationship between school leadership and organizational effectiveness in public sector institutions through a qualitative research approach. The study aimed to understand how leadership practices influence institutional performance, teacher motivation, academic management, and organizational climate within public sector schools. An exploratory research design was employed to gain in-depth insights into the lived experiences and perceptions of educational leaders and teachers. Data were collected through 10 Key Informant Interviews (KIIs) conducted with school principals, vice principals, and senior teachers selected through purposive sampling. The collected data were analyzed using thematic analysis to identify recurring patterns and themes related to leadership and organizational effectiveness. The findings revealed that transformational and instructional leadership practices play a significant role in enhancing organizational effectiveness by promoting teacher motivation, collaboration, academic accountability, and institutional vision. The study also identified major challenges affecting leadership effectiveness, including bureaucratic constraints, centralized decision-making, political interference, and resource limitations. Additionally, a positive organizational climate and community engagement emerged as important contributors to institutional success. The study concludes that effective school leadership is essential for improving organizational effectiveness in public sector institutions. It recommends strengthening leadership training, increasing institutional autonomy, and promoting participatory management practices to enhance educational quality and institutional performance in Pakistan.